2005
DOI: 10.2535/ofaj.82.95
|View full text |Cite
|
Sign up to set email alerts
|

Rare Courses of the Mandibular Canal in the Molar Regions of the Human Mandible: A Cadaveric Study

Abstract: The inferior alveolar artery, vein and nerve send some branches to the molar teeth via the mandibular canal to the mental foramen. The present study attempted to define the presence and course of the mandibular canal in the mandible with the alveolar process by macroscopic cadaveric dissection and computerized tomography (CT) in order to provide information that might prevent injuries to vessels and nerves at risk during root canal treatment. We identified the position of the mandibular canal within a 30% rati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
30
2
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 14 publications
4
30
2
1
Order By: Relevance
“…Related to the distance between the MC from second molar roots, the findings of this study were a little higher than the reports of Bürklein et al (2.8 mm), but considerably different when compared with the study of Sato et al (2005) performed in panoramic radiographs (0.7 mm). The distance from the first molar roots was similar to that reported in some studies (Bornstein et al, 2011;Bürklein et al); however, it was significantly different from the findings of Koivisto et al (2011) (2.3mm) and Sato et al (1 mm).…”
Section: Discussioncontrasting
confidence: 94%
“…Related to the distance between the MC from second molar roots, the findings of this study were a little higher than the reports of Bürklein et al (2.8 mm), but considerably different when compared with the study of Sato et al (2005) performed in panoramic radiographs (0.7 mm). The distance from the first molar roots was similar to that reported in some studies (Bornstein et al, 2011;Bürklein et al); however, it was significantly different from the findings of Koivisto et al (2011) (2.3mm) and Sato et al (1 mm).…”
Section: Discussioncontrasting
confidence: 94%
“…Other studies have evaluated the mandibular canal on cadavers (15)(16)(17). Denio et al (15) used sectioning on 22 mandibles to examine the relationship of the mandibular canal to root apices, finding that the mandibular second premolar Figure 1.…”
Section: Discussionmentioning
confidence: 99%
“…Ikeda et al [6] conducted similar cadaver study and reported that canal is approximately 3.4 mm wide. Sato et al [7] examined 75 adult Japanese cadavers' mandibles and concluded that vertical diameter of MC was about 5 mm. Anterior to the mental foramen the MC is referred to as the incisive canal [8][9][10][11][12][13].…”
Section: Anatomy Of the Mandibular Canal (Mc)mentioning
confidence: 99%
“…Denio et al [30] evaluated 22 cadavers and found the mean distance of the MC to the apices of mandibular second molar, the first molar and premolars were 3.7, 6.9, and 4.7 mm, respectively. Sato with coauthors [7] defined the presence and course of the MC using macroscopic cadaveric dissection and CT or panoramic X-ray observation. Panoramic X-ray observation revealed that the vertical position of MC was closer to the apices of the first and the second molars than that to the distance of inferior border of mandible.…”
Section: A B C Dmentioning
confidence: 99%